ALTERNATIVE FORMULATION OF PHYSICAL LAWS OF MOTION - Sudiarta, I Wayan (Indonesian Physical Review, 2020)
The purpose of this paper is to present a logical, consistent and understandable alternative formulation of physical laws of motion. This paper gives also a different view and understanding of physical laws of motion. This new point of view gives a deeper understanding about our universe. The central idea of this formulation is the concept of momentum and its conservation. This idea is emphasized in this paper. It is shown that Newton's laws of motion are given as a consequence of the law of conservation of momentum.